"Against the Biggest Buccaneering Enterprise in Living History": Krishna Menon and the Colonial Response to International Crisis. Issue 3 (1st October 2020) - Moscovitch, Brant
Abstract: This article uses London-based South Asian and other colonial students as lenses to examine the development of anti-colonial alliances during the interwar period. It focuses on responses to three international crises in the 1930s: the Second Italian-Abyssinian War [1935–36], the Spanish Civil War [1936–39] and the Second Sino-Japanese War [1937–45]. The overarching argument is that these international crises stimulated increased cooperation between London-based students and activists from South Asia, as well as Africa and peoples of African descent, and China, and identifies V.K. Krishna Menon and his anti-colonial India League as crucial to facilitating interactions. The article concludes by asserting that efforts to form transnational alliances also highlighted widening divergences between the representatives of colonies, foreshadowing the challenges of creating and maintaining South-South affinities in the postcolonial period.